PENGARUH PERSEPSI KEGUNAAN DAN PERSEPSI KEMUDAHAN TERHADAP MINAT PENGGUNAAN BRImo (BRI mobile) (Pada Pedagang Sembako di Pasar Tanjung Kabupaten Jember) - Edwina Nisrina Salsabila; Hety Mustika Ani; Mukhamad Zulianto (Badung Bali: Politeknik Negeri Bali, 2023)
This study aims to analyze the factors that can influence the perception of staple food traders in the Tanjung market about interest in using BRImo through attitude towards using, using the TAM (Technology Acceptance Model) approach. These factors include perceived usefulness, perceived ease of use, and attitude towards using as Intervening variables. This research was conducted by distributing questionnaires to food traders in Tanjung market, Jember regency. Sample determination in this study used the Simple Random Sampling method. The questionnaire was distributed to 109 food traders in Tanjung market who qualified as samples and analyzed using SPSS (Statistical Package for the Social Sciences).The test showed that: (1) perceived usability had a significant effect on interest in use; (2) perceived convenience has a significant effect on interest in use; (3) attitude toward using has a significant effect on interest in use; (4) perceived usefulness of interest through attitude toward using has a significant effect; (5) The perception of ease of interest through attitude toward using does not have a significant effect.